2016
DOI: 10.18203/2349-3259.ijct20161413
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of randomized clinical trials leading to new drug approvals in India and USA

Abstract: <p class="abstract"><strong><span lang="EN-US">Background:</span></strong>To analyse the number of randomized clinical trials and subsequent new drug approvals in India and USA.</p><p class="abstract"><strong>Methods:</strong> Data was collected for completed randomized clinical trials done by multinational in India and USA from www.clinicaltrials.gov during the period from 1/1/2009 to 31/08/2014 and the subsequent new drug approvals from 1/1/2010 to 31/10/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The unethical behaviour of few pharmaceutical agencies with regards to medical trials was also detected [ 5 ]. Since India has a sizeable native population, Indian pharmaceutical industries focus on new drug discovery and development for cost-effective trials, which would help to increase the number of clinical trials in India [ 6 , 7 ]. However, it is reported that some trials were conducted in an unethical manner without any regulations and do not hold any ethical approval [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The unethical behaviour of few pharmaceutical agencies with regards to medical trials was also detected [ 5 ]. Since India has a sizeable native population, Indian pharmaceutical industries focus on new drug discovery and development for cost-effective trials, which would help to increase the number of clinical trials in India [ 6 , 7 ]. However, it is reported that some trials were conducted in an unethical manner without any regulations and do not hold any ethical approval [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Due to the of presence large treatment-native population and cost-effective trials, the Indian pharmaceutical industries focused on new drug discovery and development which resulted in an increase in the number of clinical trials done in India. 7,8 But such trials were conducted without regulations and necessary ethics approval. To ensure transparency, accountability and accessibility of clinical trials, it is mandatory to register clinical trials in India at Clinical Trial Registry -India (CTRI) website www.ctri.nic.in, hosted by National Institute of Medical Statistics (NIMS).…”
Section: Introductionmentioning
confidence: 99%